PROGRAM EKSTRAKURIKULER DI SEKOLAH MENENGAH ATAS (SMA) SEDERAJAT - Zahra, Alya; Sriwahyuni, Eci (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
Education at the Senior High School (SMA) level has an important role in shaping students' character and potential. In addition to in-class learning activities, extracurricular programs are an integral part of the educational experience. This program not only offers additional insight, but also provides a platform for studentsto develop skills, talents and social values. The method used in this research is Systematic Literature Review (SLR) which is a method used to refer to research methodology or specific research and development carried out to collect and evaluate research related to a particular topic focus, with six stages, namely planning (determining the object research, literature search, assessment of inclusion and exclusion criteria, quality assessment, data collection, and data analysis. The aim of this research is to find out the types of extracurriculars implemented in high schoolsand equivalents, what obstacles are faced in extracurricular activities in high schools and equivalents. Evaluation of what kind of extracurricular activities are carried out in high schools and equivalents. Based on the results of the analysis of the types of extracurricular activities that are most widely implemented in high schools andequivalents, there are four groups, namely scout extracurriculars, sports, arts, languages and other types of extracurriculars in accordance with the requirements. interests and talents of students at the school. Obstacles in implementing extracurricular activities in high school can be grouped into external factors and internal factors. The types of evaluation carried out are evaluations carried out at the beginning of the activity in the form of selection, evaluations carried out during the activity process and continuous evaluations carried out periodically and continuously.